Connecting with connexins. (28th June 2013) - Williams, Penelope; Memon, Aamir; Sinha, Tapati; Fryer, Alan
Abstract: We describe a case of an 18‐year‐old woman with congenital sensorineural deafness who presented to the dermatology clinic with asymptomatic thickening of the skin over the palmar aspect of her hands and feet. An examination revealed palmoplantar keratoderma of the palms and soles of the feet with no pseudoainhum. Her father wore a hearing aid and his deafness had been thought to be acquired. Mutation analysis of the connexin 26 gene revealed that she carried a paternally inherited mutation, p.Asp46Glu and a maternally inherited M34T variant. The p.Asp46Glu mutation has been described in a family exhibiting non‐syndromic autosomal dominant deafness. Although the M34T variant has been described as a non‐pathogenic variant or with a very mild phenotype only, its combination with the p.Asp46Glu mutation may account for her mild cutaneous phenotype with later clinical presentation